Tectonic evolution of the Southern part of Aravalli Mountain Belt and its environs: possible causes and time constraints - Mamtani, Manish A.; Karanth, R. V.; Merh, Sukumar S.; Greiling, Reinhard O. (Gondwana research, 2000)
Structural studies on Proterozoic rocks belonging to the Lunavada Group, Southern Aravalli Mountain Belt (SAMB), India, have shown that they underwent three episodes of deformation which have led to the formation of various regional scale interference patterns. Whilst the northern parts of the SAMB underwent brittle-ductile deformation, the southern portion underwent more ductile deformation. On the basis of structural as well as metamorphic studies it has been established earlier that the region was subjected to uplift orogenesis during its evolutionary history. In the present paper an attempt is made to visualize the possible causes that led to deformation of the SAMB, the structural geology of which has been established by the authors, and to constraint the timing of these events on the basis of already available geochronological data. A “working-hypothesis” is proposed according to which it is suggested that deformation of the SAMB is a result of the accretion of the three protocontinents viz. Aravalli, Dharwar and Singhbhum during the Mesoproterozoic. It is envisaged that the accretion of Aravalli and Singhbhum Protocontinents occurred between 1600 and 1400 Ma along the NE-SW trending Son Suture and this event led to development of NE-SW trending structures in the SAMB. Suturing of Aravalli and Dharwar Protocontinents between 1400 and 935 Ma along the E-W Narmada Suture was responsible for the E-W to NW-SE trending D3 structures of the SAMB. It is postulated that the Satpura orogeny which resulted in deformation of rocks in Satpura mountain range lying to the south of Narmada Suture was coeval with the accretion of Aravalli and Dharwar Protocontinents.